Double Jeopardy: Truncus Arteriosus with Obstructed Infracardiac Total Anomalous Pulmonary Venous Connection - Anil Kumar Singhi; Mrinal Bandhu Das; Soumya Kanti Mohapatra; Soumen Das; Anish Nath; Dipanjan Chatterjee (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2023)
Truncus arteriosus (TA) is a congenital cyanotic heart disease with admixture physiology at the great arterial level. It can have associated anomalies of the pulmonary arteries, truncal valve narrowing, etc., Total pulmonary venous anomalous drainage associated with TA is extremely rare. We report a sick young infant who presented with type I TA and obstructed infracardiac total anomalous pulmonary venous return.